Two women lying on a blanket - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows two women outside lying together on a blanket in the grass. They are wearing shorts and teeshirts. The woman toward the right wears a teeshirt that reads, "Pat Benatar".